Coffee sustainability: leveraging collaborative breeding for variety improvement - Ngure, Godfrey M.; Watanabe, Kazuo N. (Frontiers in Sustainable Food Systems, 2024)
The sustainability of global coffee supply is threatened by production challenges worsening with every decade since the turn of the 21st century. Coffee is among the most popular beverages in the world, and its production supports livelihoods of millions of people, mostly smallholder farmers. With a global market value exceeding US$130 billion, the coffee industry is a source of export revenue for producing countries, the majority of which are developing nations in the Global South. Climate change, pests, and diseases continue to hamper productivity, profitability, and countries’ competitiveness in the global market. At the same time, the global demand for coffee continues to rise. A crucial pillar to safeguarding the future of coffee is continuously developing improved varieties suitable for the changing environment, and that address the needs of farmers and the industry. Yet, most national breeding programs are grossly out of touch with climate change reality and market dynamics. Working in isolation, these programs are constrained by unstable funding, limited sources of genetic variability, and inaccessibility of modern technologies necessary to accelerate the breeding process. We review here key production challenges, status of genetic diversity, and breeding approaches. Additionally, we explore opportunities in leveraging a pre-competitive collaborative breeding approach encompassing sharing of germplasm, and cross-border multi-environment trials in developing next-generation cultivars. We argue that breeding efforts should be informed by the needs of all the stakeholders in the supply chain including researchers, smallholder farmers, small and medium-sized enterprises investing in coffee processing and roasting, and consumers. Using emerging and reviving producers in Southeast Asia and Eastern Africa as a model, we explore how a paradigm shift in coffee breeding from the historically nation-centric approach to a more forward-looking collaborative model could improve the efficiency of variety improvement in face of climate change and growing market demand.